Overexpression of nitrate transporter OsNRT2.1 enhances nitrate‐dependent root elongation - Naz, Misbah; Luo, Bingbing; Guo, Xueya; Li, Bin; Chen, Jingguang; Fan, Xiaorong (MDPI, 2019)
Root morphology is essential for plant survival. NO3− is not only a nutrient, but also a signal substance affecting root growth in plants. However, the mechanism of NO3−-mediated root growth in rice remains unclear. In this study, we investigated the effect of OsNRT2.1 on root elongation and nitrate signaling-mediated auxin transport using OsNRT2.1 overexpression lines. We observed that the overexpression of OsNRT2.1 increased the total root length in rice, including the seminal root length, total adventitious root length, and total lateral root length in seminal roots and adventitious roots under 0.5-mM NO3− conditions, but not under 0.5-mM NH4+ conditions. Compared with wild type (WT), the 15NO3− influx rate of OsNRT2.1 transgenic lines increased by 24.3%, and the expressions of auxin transporter genes (OsPIN1a/b/c and OsPIN2) also increased significantly under 0.5-mM NO3− conditions. There were no significant differences in root length, ß-glucuronidase (GUS) activity, and the expressions of OsPIN1a/b/c and OsPIN2 in the pDR5